2021
DOI: 10.1155/2021/5586030
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Acute Upper Gastrointestinal Bleeding in Xingtai City

Abstract: Background and Aims. The coronavirus disease 2019 (COVID-19) has severely impacted the daily practice of gastrointestinal endoscopy worldwide. Most endoscopy centers in China were shut down in late January 2020. We investigated the impact of the shutdown on acute upper gastrointestinal bleeding (AUGIB) events in Xingtai City, Hebei Province, China. Methods. A web-based survey collected information on gastroscopy workload and AUGIB events. The study period was from 4 weeks before to 4 weeks after lockdown initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 15 publications
4
10
0
Order By: Relevance
“…This supports the notion that patients with a variety of illnesses, including UGIB, avoided hospital presentation during the pandemic 31,32 . Our finding of patients admitted during the COVID‐19 period being less likely to under endoscopy is also in keeping with prior reports 28,30 . We also found that patients in the study period were less likely to undergo second endoscopy in the unadjusted model.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This supports the notion that patients with a variety of illnesses, including UGIB, avoided hospital presentation during the pandemic 31,32 . Our finding of patients admitted during the COVID‐19 period being less likely to under endoscopy is also in keeping with prior reports 28,30 . We also found that patients in the study period were less likely to undergo second endoscopy in the unadjusted model.…”
Section: Discussionsupporting
confidence: 89%
“…One notable finding was that there were fewer presentations per month for UGIB during the first wave of the pandemic compared with prior years, similar to previous studies in Xingtai City, New York City, London, and Hong Kong 27–30 . The percentage of patients with UGIB of all GIM and ICU admissions in our study was not meaningfully different between the COVID‐19 and control groups.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A survey of 60 public hospitals reported substantially fewer (40.7%) cases of GI bleeding after a lockdown was implemented in Austria [ 14 ]. Another survey of 12 Chinese hospitals also revealed a 55.7% decline in the number of upper GI bleeding cases [ 15 ]. Besides their willingness to seek help, patients with GI bleeding may have further found that it was more difficult to access appropriate treatment during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 global pandemic appeared in China during the last days of 2019 and spread very fast in all countries during the spring of 2020 [1][2][3][4]. The pandemic has had multiple negative consequences on the healthcare system, which mainly focused on lockdown measures, the need for dedicated beds, additional personnel, specific access routes for SARS-CoV-2 patients, and overwhelmed emergency rooms [2,3].…”
Section: Introductionmentioning
confidence: 99%